Meme Discourse as an Object of Linguocognitive Modelling - I. V. Rogozina; N. Yu. Buhner (Дискурс)
Introduction. The  goal  of  this  study  is  to  gain  new  insights  into  meme  discourse  by reconstructing  its  linguocognitive  model,  based  on  the  properties  and  characteristics  of memes, relevant for Internet communicators.Methodology and sources. In order to reconstruct the meme-discourse model the authors combine  the  method  of  linguocognitive  modelling  with  the  technique  of  fragmenting  the respondents'  answers  into  motivational  explications  as  units  of  measurement  for  the obtained  data.  The  meme  discourse  model  is  based  on  the  answers  of  100  students  at I.I. Polzunov Altai State Technical University – “Why do you use memes when communicating?” The  choice  of  respondents  is  determined  by  their studying  at  the  Faculty  of  Information Technology and being advanced Internet users.Results  and  discussion. Motivational  explications  of  Internet  users  of  why  they  resort  to memes to communicate serve as language material for inferring cognitive foundations for using memes. The most  significant  cognitive  foundation  for  the  use  of  memes  by communicators is the effectiveness of the impact they make (47.3 %). The second cognitive foundation is related to communication productivity: memes help to establish and maintain communication  (20,9 %).  The  third  one  is  the  functionality  of  memes,  which  facilitates  the transmission of content (17,1 %). The fourth one is the format suitable for conveying thoughts and feelings (14,7 %). Based on the concept of discourse, proposed by T. van Dijk and the reconstructed model the authors gain new insights into the nature of meme-discourse.Conclusion. The  main  conceptual  conclusion  regarding  meme-discourse  is  that,  as  a complex communicative phenomenon, it appears to be an important component of sociocultural interaction for its participants. Both the goal and the result of this interaction is to create  a  positive  type  of  social  context  maintained  and  preserved  through  mutual understanding  between  the  communicants.  Memes  facilitate  finding  common  points  of contact serving as a “package” of  positive  emotions  for  communicators’  thoughts  and feelings.  In  this  way  communicants  produce  meme-discourse  as  an  actual  referential context to share their worldview.